Sustainable Development Objectives and University Social Responsibility integrated in a Strategic Planning model - Aguilar Barojas, Saraí (Emerging Trends in Education, 2022)
The Sustainable Development Goals (SDGs) are a call from the United Nations Organization for all countries to adopt the necessary measures to improve various situations that have deteriorated the environment and delayed the development of peoples, peace and prosperity. In this context, the passage of young people through the university is a crucial moment of awareness and education on these issues for which a strategic planning model is proposed that integrates the SDGs with University Social Responsibility (RSU) in order to guarantee its approach and compliance. The model presented in a first diagram is dynamic and has three planes. In the center are the SDGs in addition to the mission, vision and institutional values ​​linked to USR. In a second plane are the elements of planning, such as objectives, strategies and goals. A third plane considers the evaluation of the structure, the processes and the results. The three planes converge in the four university substantive functions. A second diagram shows the interactions between the elements considered. The adaptation of this model makes it possible to point out and keep focused on the SDGs to add universities to the challenge of the world goal set for 2030. Keywords: Model, University Social Responsibility, Sustainable development goals, Strategic planning.